Rice peptide with amino acid substitution inhibits biofilm formation by Porphyromonas gingivalis and Fusobacterium nucleatum. (January 2021) - Matsugishi, Aoi; Aoki-Nonaka, Yukari; Yokoji-Takeuchi, Mai; Yamada-Hara, Miki; Mikami, Yoshikazu; Hayatsu, Manabu; Terao, Yutaka; Domon, Hisanori; Taniguchi, Masayuki; Takahashi, Naoki; Yamazaki, Kazuhisa; Tabeta, Koichi
Highlights: Rice peptide inhibited biofilm formation of periodontopathic bacteria. The amino acid substitution of rice peptide was stronger inhibitor of biofilm. The substitution had stronger bactericidal activity by membrane disruption. The amino acid replacement reinforced the electostatic interaction with bacteria. We have shown the potential for the use of these peptides in periodontal therapy. Abstract: Objective: Rice peptide has antibacterial properties that have been tested in planktonic bacterial culture. However, bacteria form biofilm at disease sites and are resistant to antibacterial agents. The aim of this study was to clarify the mechanisms of action of rice peptide and its amino acid substitution against periodontopathic bacteria and their antibiofilm effects. Design: Porphyromonas gingivalis and Fusobacterium nucleatum were treated with AmyI-1-18 rice peptide or its arginine-substituted analog, G12R, under anaerobic conditions. The amount of biofilm was evaluated by crystal violet staining. The integrity of the bacteria cytoplasmic membrane was studied in a propidium iodide (PI) stain assay and transmission electron microscopy (TEM). Results: Both AmyI-1-18 and G12R inhibited biofilm formation of P. gingivalis and F. nucleatum; in particular, G12R inhibited F. nucleatum at lower concentrations. However, neither peptide eradicated established biofilms significantly. According to the minimum inhibitory concentration and minimum bactericidal concentration against P. gingivalis, AmyI-1-18 has bacteriostatic properties and G12R has bactericidal activity, and both peptides showed bactericidal activity against F. nucleatum. PI staining and TEM analysis indicated that membrane disruption by G12R was enhanced, which suggests that the replacement amino acid reinforced the electostatic interaction between the peptide and bacteria by increase of cationic charge and α-helix content. Conclusions: Rice peptide inhibited biofilm formation of P. gingivalis and F. nucleatum, and bactericidal activity via membrane destruction was enhanced by amino acid substitution.